Papers published in Zootaxa concerning Neuropterida - Letardi, Agostino; Bowles, David E.; Liu, Xingyue (Zootaxa, 2021)
In the first twenty years of the publication of Zootaxa, more than two hundred papers have appeared in this journal that address the Neuropterida, which collectively includes the [Neuroptera+Raphidioptera]+Megaloptera sections (initially “Minor orders” section). A dozen submitted manuscripts were rejected before the review process, and another dozen submissions were rejected following the peer review process. Additional content and general submission history of these contributions is summarized here. These various contributions highlight the growing body of research on the Neuropterida and the importance of Zootaxa as a key journal for publishing and disseminating this research.